2016
DOI: 10.1177/1526924816655073
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Clostridium Difficile Diarrhea in Patients With Solid Organ Transplantation

Abstract: Liver transplant recipients presented the highest incidence. Risk factors for CDI were previous treatment with PPIs, immunosuppressive regimen containing mycophenolate, prior hospitalization, and prior antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
(92 reference statements)
3
9
0
Order By: Relevance
“…We observed that while CDI may occur during the immediate post‐transplant period, the majority of cases occur beyond 30 days, and many during 2‐24 months after transplantation. This observation is in line with a previous report . Many of the risk factors for CDI after SOT are observed during this period, including hospitalization, antibiotic use, augmented immunosuppressive therapies, and use of proton‐pump inhibitors …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that while CDI may occur during the immediate post‐transplant period, the majority of cases occur beyond 30 days, and many during 2‐24 months after transplantation. This observation is in line with a previous report . Many of the risk factors for CDI after SOT are observed during this period, including hospitalization, antibiotic use, augmented immunosuppressive therapies, and use of proton‐pump inhibitors …”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrates the common occurrence of CDI in HT recipients, with one in every 10 patients developing this infection during the post‐transplant period. This is similar to the incidence rates of CDI in HT recipients as reported in the literature . We observed that while CDI may occur during the immediate post‐transplant period, the majority of cases occur beyond 30 days, and many during 2‐24 months after transplantation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is the situation with Clostridium difficile , a major cause of gut infection in individuals following antibiotic treatment 54, 55 and whose infection is associated with a reduction in gut microbiota diversity 56 . Given C. difficile ’s low susceptibility to antibiotics, the best way for fighting recurrent infections caused by this pathogen is restoring the functionality of the gut microbiota via fecal transplantation 5760 .…”
Section: Multi-hierarchical Antibiotic Selection Of Bacterial Populatmentioning
confidence: 99%
“…In another study focused on solid organ transplant recipients, predominately kidney transplant recipients, 25% to 40% of etiologies were identified . Norovirus has been reported to account for approximately 25% of post‐transplant diarrhea cases and C difficile infection occurs in 2% to 7% of kidney transplant recipients …”
Section: Introductionmentioning
confidence: 99%